A facile chemical process to form an ultrathin hydroxyapatite layer with a customizable silver‐releasing function on a titanium implant. Issue 3 (20th September 2021) - Ohtsu, Naofumi; Kakuchi, Yuko; Takahara, Toyofumi; Yoshida, Yutaka
Abstract: Silver‐containing hydroxyapatite (Ag/HAp) layer on a bioinert material provides both bioactive and antibacterial properties; however, the Ag release duration needs to be customized to a patient's age and metabolism for minimizing the toxic effects. Herein, we present a facile chemical process to produce an ultrathin Ag/HAp layer on a Ti implant with a customized Ag‐releasing profile. The process involves the following steps: preparation of a slurry‐type reagent by mixing calcium phosphate powder with an aqueous AgNO3 solution, burying a Ti substrate in the slurry, and heating the slurry in air. An HAp layer, approximately 50 nm thick, with Ag particle deposits was obtained using this process. The Ag‐particle content can be varied by adjusting the concentration of AgNO3 solution used for slurry preparation, resulting in different Ag‐release profiles in a physiological solution. For instance, Ag release was retained for up to 30 days when 100 mM AgNO3 was used, whereas the release lasted 15 days when 10 mM AgNO3 was used. The duration of the antibacterial activity varied accordingly, but Ag‐release‐derived cytotoxicity was not observed irrespective of the AgNO3 concentration. In addition, differentiation of osteoblast‐like cells was facilitated owing to the formation of the HAp layer. Thus, the chemical process presented in this study allows the production—at a clinical site—of an Ag/HAp layer customized to the patient's needs.